HUBUNGAN PERSONAL HYGIENE DAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) DENGAN KEJADIAN DERMATITIS KONTAK PADA PETUGAS PENGANGKUT SAMPAH DI TEMPAT PEMBUANGAN AKHIR (TPA) TADUKAN RAG - MARBUN, VIKTOR EDYWARD; Sembiring, Johannes; syafitri, anggun (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Contact dermatitis is dermatitis caused by the presence of irritants or allergens attached to the skin. Epidemiological data in Indonesia shows that 97% of 389 cases of skin disease are contact dermatitis, 66.3% of these cases are irritant contact dermatitis and 33.7% are allergic contact dermatitis. This study aims to determine the relationship between personal hygiene and the use of personal protective equipment (PPE) with the incidence of contact dermatitis in waste collectors at the Tadukan Raga Deli Serdang final disposal site (TPA) in 2023. This study used a quantitative approach with a cross sectional study design. The research was conducted in March 2023 – June 2023 at the Tadukan Raga landfill in Tanjung Morawa. The population of this study were all garbage collectors at the Tadukan Raga TPA. The number of samples in this study were 43 people with the sampling technique being total sampling. Data was collected using a questionnaire with interviews. Data analysis was performed univariately and bivariately with the chi-Square test. The results showed that the variables associated with the incidence of contact dermatitis were: personal hygiene (pvalue=0.004), personal protective equipment (pvalue=0.013). There is a relationship between personal hygiene and the use of personal protective equipment (PPE) with the incidence of contact dermatitis.